Development and evaluation of low head and minimum pressure drop equipment for fertilizer application through drip irrigation system - KUMAR, SANTOSH; SINGH, K G; SINGLA, CHETAN (The Indian Journal of Agricultural Sciences, 2013)
The different methods of fertilizer application through drip irrigation system are By-pass tank, Venturi and pumpsystem and the venturi is most commonly used for fertilizer application through drip irrigation system, the main limitations of venturi are large pressure drop and high head requirement for its operation. So equipment called as orifice meter was developed for the fertigation purpose in the drip irrigation system which operates at inlet pressure below 1 kg/cm2. Six different sizes of orifice meters developed and evaluated at the Research farm, Department of Soil and Water Engineering, Punjab Agricultural University, Ludhiana. Four orifices having diameter 3.18 mm and thickness 25.4 mm, 19.05 mm, 12.7 mm and 9.53 mm and two orifices of diameters 2.38 mm and 1.59 mm with thickness 12.7 mm. were evaluated in the range of 0.42 to 0.944 kg/cm2. The maximum injection rate was of 45 lph of orifice meter having diameter 3.18 mm and thickness 12.7 mm operating at inlet pressure 0.702 kg/cm2 found to be best. The developed equipment is also suitable for farmers having small land holdings or in greenhouse.